Identification and utilization of medicinal plants in the village of the Kesatuan Pemangkuan Hutan (KPH) Saradan, Madiun - Prameswari, Yuanita; Dewi, Nurul Kusuma; Yuhanna, Wachidatul Linda (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2023)
The diversity of plants in Indonesia means that many plants have the potential to be used as medicine by the community. Because of its potential as a medicine, many people do not know about it, so it is important to study it. The use of medicinal plants by the community has been passed down from generation to generation, so there is still a lack of documentation regarding the use of medicinal plants. This study aims to identify medicinal plants in the Saradan Kesatuan Pemangkuan Hutan (KPH) area as well as the utilization of plants that are often used as medicine by the community in the Saradan KPH area. The research was conducted in March 2022. Ethnobotanical data were collected using the roaming method and the structured interview method using ethnobotanical interview sheets. Identification of medicinal plants using the help of books on medicinal plants by Widyaningrum. The selection of respondents was carried out randomly, according to the study, which documented 32 species of medicinal plants from 18 families. The most commonly found families of medicinal plants are the Zingiberaceae and Euphorbiaceae families. The leaves are the most useful part of the plant. and the method of treatment with medicinal plants is mostly done by boiling and pounding. The medicinal plant diversity documented in KPH Saradan village is 32 species. Ocimum basilicum L., Alpinia Galanga L. Willd., Zingiber officinale Rosc., and Curcuma domestica Val. medicinal plants that are most widely used by the community around KPH Saradan.